Strategi Pemberdayaan Komunitas Lokal: Menuju Kemandirian Daerah - Trijono, Lambang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2001)
Rhetorically, local authonomy and societal empowerment are mutually required. The lacking of structural and political understanding of the notion of empowernment has allowed the sustenance of status quo.